A taxonomic revision of the genus Bergeranthus Schwantes (Mesembryanthemaceae) in South Africa - Dold, Anthony P (Rhodes University, Faculty of Science, Botany Department, 2002)
The genus Bergeranthus Schwantes comprises ten species ofleaf-succulent Mesembryanthemaceae that are centred in the Albany centre of endemism and restricted to the Eastern Cape Province of South Africa. No taxonomic revision of the genus, or key to the species of Bergeranthus, has been undertaken since its description by Schwantes in 1926. The species concepts are mostly based on single, or at best severaL cultivated plants and are notoriously narrow and in some cases incorrect. Louisa Bolus described five of the ten currently recognized species of Bergeranthus (as well as B. cookii, B.firmus, B. glenensis, B.jamesii, and B. longisepalus) from cultivated plants that she had never seen in the wild. This narrow species concept, compounded by morphological change that occurs in response to environmental factors, presents an assemblage of ill-defmed and poorly known taxa that have been prioritised for taxonomic attention by various authors. Furthermore, the generic delimitation of Bergeranthus with the closely related genera Rhombophyllum and Hereroa is unclear and requires attention before generic revisions are attempted for all three genera. The taxonomic revision presented here is based on a study of 210 wild populations of Bergeranthus as well as cultivated representatives of these and 135 herbarium specimens. A phenetic analysis based on 36 vegetative characters was initially used to delimit taxa. Thereafter sixty-three macro- and micro-morphological characters were critically assessed for the purposes of species delimitation, amendment of existing species descriptions and the description of two new species. Macromorphological characters examined included rootstock, leaf(36), inflorescence, floral (nine), fruit (nine), seed germination and seedling characters. Micro-morphological characters examined included leaf anatomy, leaf epidermal wax layer, anther shape and point of adherence, pollen and seed characters. This revision reduces two species into synonymy and two new species, B. albomarginatus and B. nanus, are described. Existing species descriptions are improved and all species are illustrated. A key to species is provided. The reproductive biology, ecology, phytogeography and distribution data of the genus are discussed towards an improved understanding of the genus. The generic delimitation of Bergeranthus and its closest relatives, Rhombophyllum and Hereroa, are discussed based on an examination of 25 morphological characters and two phenological characters and a provisional key to genera is provided. A phylogenetic analysis of all 10 species of Bergeranthus, both species of Rhombophyllum and a single species of Hereroa (H. granulata) was undertaken to support species and generic delimitation.
Keywords: Aizoaceae -- South Africa